2018
DOI: 10.1111/cga.12273
|View full text |Cite
|
Sign up to set email alerts
|

Novel SYNGAP1 variant in a patient with intellectual disability and distinctive dysmorphisms

Abstract: We describe a novel de novo heterozygous variant in SYNGAP1 (c.1741C>T, p.R581W), identified through targeted resequencing in an 8-year-old boy with intellectual disability, autism spectrum disorder, distinctive dysmorphic features, and no seizures. Our data strongly suggest that the SYNGAP1 variant is causative of intellectual disability in this patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Previous studies have reported individuals with SYNGAP1 deleterious variants and associated phenotypes. Reported phenotypic traits have included nearly universal epilepsy and intellectual disability/developmental delay, as well as variable presence of autism spectrum disorder and physical dysmorphisms [16, 17]. However, in-depth and longitudinal clinical characterization of a cohort of individuals ascertained for pathologic SYNGAP1 variants has not been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported individuals with SYNGAP1 deleterious variants and associated phenotypes. Reported phenotypic traits have included nearly universal epilepsy and intellectual disability/developmental delay, as well as variable presence of autism spectrum disorder and physical dysmorphisms [16, 17]. However, in-depth and longitudinal clinical characterization of a cohort of individuals ascertained for pathologic SYNGAP1 variants has not been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…SYNGAP1 heterozygosity impairs sensory processing by reducing touch-related activity in the somatosensory cortex (13). Distinctive dysmorphism is observed in the SYNGAP1 mutation (14). The possible mechanism in epilepsy due to SYNGAP1 mutation is the increase in neuronal excitability caused by AMPAR activity (15).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis utilized the TruSight One Sequencing Panel kit with the MiSeq platform (Illumina, Inc., San Diego, California). Exome data alignment, variant calling, and variant annotation were assessed 3 . Copy number variants (CNVs) were calculated from log‐ratio analysis of exon depth 4 …”
Section: Figurementioning
confidence: 99%